Insights into Faculty-Librarian Collaborations around the Framework Findings from the 2018 Co-design Survey - Stöpel, Michael (2020)
Since the 1980s, assessment has been one of the most frequently investigated topics in library and information science literature, seen by librarians as a valid tool for analyzing the effectiveness and impact of teaching. With this in mind, after the Paris workshop and the rollout of the co-designed pilot courses, the AMICAL Information Literacy Committee (ILC) wanted to assess whether the courses had been successful with regard to both learning and teaching and to determine new fruits the co-designing had produced. A second, but equally important, motivation was to report back to the AMICAL Consortium, which funded and supported our project from the beginning. The main goal was to collect qualitative feedback to give insight into the projects and to build a "thick description" of the teaching experience. In order to effectively assess the course design project, as well as provide essential feedback to our stakeholders, the ILC developed and administered a survey about the co-design experience. This survey was conducted among twenty-six participants from eleven different liberal arts institutions outside the United States that are all members of the AMICAL Consortium (appendix 2A). The survey participants came from diverse countries: Lebanon, Armenia, the United Arab Emirates, Morocco, Kuwait, Italy, Switzerland, Kyrgyzstan, Bulgaria, Kosovo, and France. It is interesting to see how the teaching experience and the idea of liberal arts education unfolds within the local contexts of these different cultures as well as different disciplines. For instance, for a better understanding of classroom dynamics, aspects such as attitudes toward female teachers or methods used to teach history in different countries must be taken into account when analyzing responses.